Analisis konseptual tentang pentingnya manajemen: dalam menghadapi pengaruh lingkungan eksternal dan internal - zaskiya, malikha (Maliki Interdisciplinary Journal, 2025)
This article explains why management is important in dealing with external and internal environmental influences. Management is a process of planning, controlling, organizing, and directing. Management plays a crucial role in influencing both the external and internal environments within a company, institution, and organization, helping to regulate the company’s operations based on the impacts of both external and internal environments. The internal environment encompasses factors within the organization, such as employee skills, leadership style, work culture, and organizational structure. The external environment encompasses factors outside the organization, such as competition with other companies, changes in government regulations, economic conditions, and technological developments. All of these factors are not fixed; they are subject to change and are interconnected. Therefore, organizations must be prepared to adapt. An organization can only function well if management can leverage its internal strengths and adapt to changes occurring externally. Management plays a crucial role in determining direction and strategy, managing resources, and making decisions to ensure the organization remains competitive. This discussion emphasizes that management is a process that helps organizations survive, grow, and achieve their long-term goals. By understanding internal and external conditions, organizations can create appropriate plans and strategies and adapt to changes. This article aims to provide a simple overview of the importance of management in relation to the influence of the internal and external environment.